Primitives for building interaction protocols - Tucat, Mariano (2006)
In this paper we propose a set of protocol primitives for the implementation of interaction protocols in Multi-agent systems. These primitives are based on the performatives most frequently used for agent interaction, and provide an abstract way of achieving conversations between agents, facilitating the creation of both standard or domain dependent interaction protocols. The proposed primitives automatically handle the exchange of messages needed to achieve the expected behavior of the interactions. Thus, the agent developer avoids the burden of implementing message processing and also the creation of messages corresponding to specifics agent communication languages. Examples of specific applications for the proposed primitives will be given.